Pelatihan Keterampilan Psikologis untuk Pelatih KONI DIY - Kumala Widya Rochmani; Malida Fatimah; Ros Patriani Dewi (Devotion : Jurnal Pengabdian Psikologi, 2023)
The activity of psychological skills training aims to equip the coaches of KONI DIY with psychological skills, enabling them to fulfill their roles as coaches for athletes. The training participants are 25 KONI DIY coaches, and the training was conducted over one day on July 29, 2023. Data were analyzed through pre-tests and post-tests, with the results indicating an improvement in understanding from a pre-test score of 9.840 to a post-test score of 10.320. However, statistical analysis revealed no significant difference between the two tests, with a Sig. value of 0.179 > 0.05. In contrast, the results of the participants' reaction evaluations showed a positive emotional impact, with average scores ranging from 3.68 to 4.36 in various aspects. These findings emphasize the importance of the training material. To achieve better training outcomes, efforts are needed to make the material more engaging, allocate more time, and provide more in-depth content. In conclusion, this psychological training activity has the potential to enhance communication between coaches and athletes, despite no significant changes in knowledge.